Simple provocative maneuvers in renal transplant scintigraphy for detecting urine leak - DEDE, FUAT; TUROĞLU, HALİL TURGUT; İNANIR, SABAHAT; YEGEN, ŞEVKET CUMHUR; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER, 2007)
Urine leak in the early postoperative period following renal transplantation is a serious complication requiring early identification and aggressive intervention, which significantly reduces the morbidity and mortality. Renal transplant scintigraphy is a noninvasive method to evaluate the perfusion and function of a transplanted kidney and urinary drainage including urine leak. Here, we reported two cases in which the standard transplant renogram failed to demonstrate urine leak. The cases were referred for a diethylenetriaminepentaacetic acid renogram following the transplantation to evaluate the cause of symptoms or elevated serum creatinine level. In both the cases, urine leak was successfully detected following simple maneuvers such as diuretic administration or Foley catheter irrigation. Renal transplant scintigraphy is an effective and safe technique and the use of these simple maneuvers can enhance the diagnostic sensitivity of the transplant renogram in the detection of urine leak.
Keywords: urine leak; Tc-99m DTPA; renal scintigraphy; transplanted kidney; diuretic; catheter irrigation; COMPLICATIONS; PATIENT